The anorexic effect of DL-fenfluramine is dependent on animals' habituation to different food types - Yi, Sun Shin; Choi, SuJean (Frontiers in Integrative Neuroscience, 2022)
Background As rates of obesity and diabetes have increased dramatically over the past few decades, the use of anti-obesity drugs has now become a routine therapeutic measure. However, the pharmacological effects of chronic use of these drugs in humans frequently lead to reduced efficacy in reducing appetite and body weight through as-yet-unidentified mechanisms. An example of this can be found in animal studies where the appetite suppressant DL-fenfluramine (FEN) is chronically administered and its tolerance develops in animals and humans. The appetite effects of FEN are typically measured in several animal studies by the feeding changes in a balanced standard diet. To determine whether FEN differentially altered appetite suppression in animals with long-term expression with different macronutrient diet compositions, its anorexic effects were measured specifically in male rats that had previously been chronically maintained on normal chow (NC) or a high-fat and high-carbohydrate western diet (WD). Methods Three experiments were conducted by feeding the animals either NC or WD for 1 month to habituate them with their diet. Animals maintained on either NC or WD were subsequently offered both diet options ad libitum for a 2- or 7-day adaptation period while receiving daily systemic FEN treatment. Results The results suggested that long-term habituated food affected the food preference of animals and their appetite even after chronic systemic FEN administration. Therefore, the effectiveness and success or failure of repeated use of chronic anti-obesity drugs may depend on habituated food type. Conclusion The appetite suppressant effect was found to be determined by the palatability of a specific macronutrient and the habituated food rather than by a change in the concentration of the administered FEN. This results in a critical analysis of the rationale for taking medication considering the patient's past dietary habits to achieve successful weight loss.